The Correlations Between MRI Perfusion, Diffusion Parameters, and 18F-FDG PET Metabolic Parameters in Primary Head-and-Neck Cancer: A Cross-Sectional Analysis in Single Institute. Issue 47 (November 2015) - Han, Miran; Kim, Sun Yong; Lee, Su Jin; Choi, Jin Wook
Abstract : Abstract: This study aimed to investigate the relationships among parameters from dynamic contrast-enhanced (DCE) MRI, diffusion-weighted MRI (DWI), and 18 F-fluorodeoxyglucose ( 18 F-FDG) PET in patients with primary head-and-neck squamous cell carcinoma (HNSCC). A total of 34 patients with primary HNSCC underwent DCE-MRI, DWI, and 18 F-FDG PET before treatment. The perfusion parameters (Ktrans, Ktransmax, Kep, Ve, Vp, and AUC60 ) from DCE-MRI and ADC (ADCmean, ADCmin ) values from DWI were calculated within the manually placed ROI around the main tumor. Standardized uptake value (SUVmax, SUVmean ), metabolic tumor volume (MTV), and total lesion glycolysis (TLG = SUVmean × MTV) were calculated with thresholds of 3.0 SUV. The associations between parameters were evaluated by Pearson correlation analysis. Significant correlations were identified between Ktrans and Kep ( r = 0.631), Ktrans and Ve ( r = 0.603), Ktrans and ADCmean ( r = 0.438), Ktransmax and Kep ( r = 0.667), Ktransmax and Vp ( r = 0.351), Ve and AUC60 ( r = 0.364), Ve and ADCmean ( r = 0.590), and Ve and ADCmin ( r = 0.361). ADCmin was reversely correlated with TLG ( r = –0.347). Tumor volume was significantly associated with Ktransmax ( r = 0.348). The demonstrated relationships among parameters from DCE, DWI, and 18 F-FDG PET suggest complex interactions among tumor biologic characteristics. Each diagnostic technique may provide complementary information for HNSCC.